Cloning of fusion protein gene of Newcastle disease virus into a baculovirus derived bacmid shuttle vector, in order to express it in insect cell line - Hashemzadeh MS; Shafaati MR; Dorostkar R (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2015)
Abstract Background: Newcastle disease virus (NDV) is one of the major pathogens in poultry and vaccination is intended to control the disease, as an effective solution, yet. Fusion protein (F) on surface of NDV, has a fundamental role in virus pathogenicity and can induce protective immunity, alone. With this background, here our aim was to construct a baculovirus derived recombinant bacmid shuttle vector (encoding F-protein) in order to express it in insect cell line. Materials and Methods: In this experimental study, at first complete F gene from avirulent strain La Sota of NDV was amplified by RT-PCR to produce F cDNA. The amplicon was cloned into T/A cloning vector and afterwards into pFastBac Dual donor plasmid. After the verification of cloning process by two methods, PCR and enzymatic digestion analysis, the accuracy of F gene sequence was confirmed by sequencing. Finally, F-containing recombinant bacmid was subsequently generated in DH10Bac cell and the construct production was confirmed by a special PCR panel, using F specific primers and M13 universal primers. Results: Analysis of confirmatory tests showed that the recombinant bacmid, expressing of F-protein gene in correct sequence and framework, has been constructed successfully. Conclusion: The product of this F-containing recombinant bacmid, in addition to its independent application in the induction of protective immunity, can be used with the other individual recombinant baculoviruses, expressing HN and NP genes to produce NDV-VLPs in insect cell line.